Stress factor – dependent differences in molecular mechanisms of premature cell senescence - Petrova, N.V.; Velichko, A.K.; Petrova, N.V.; Razin, S.V.; Kantidze, O.L. (Вiopolymers and Cell, 2015)
Cell senescence is an established cell stress response in the form of a permanent proliferation arrest accompanied by a complex phenotype. Senescent cells share several crucial features, such as lack of DNA synthesis, increased senescence-associated β-galactosidase activity and upregulation of cyclin-dependent kinase inhibitors. Most of these universal senescence markers are indicative not only for cell senescence but for other types of growth arrest as well. Along with ubiquitous markers, cell senescence has accessory characteristics, which mostly depend on senescence-inducing stimulus and/or cell type. Here, we review main markers and mechanisms involved in the induction of cell senescence with a focus on stress factor-dependent differences in signaling pathways activated in senescence. Клітинне старіння є відповіддю клітини на стрес у вигляді перманентного арешту проліферації, супроводжуваного комплексом фенотипічних змін. Найбільш важливими ознаками клітинного старіння є відсутність синтезу ДНК, збільшення активності асоційованої зі старінням β-галактозидази і збільшення експресії інгібіторів циклин-залежних кіназ. Ці універсальні маркери клітинного старіння характерні також і для інших типів арешту проліферації клітин. Поряд з універсальними маркерами клітинне старіння має додаткові характеристики, які більшою мірою залежать від фактора, що індукує старіння та / або типу клітин. У цьому огляді ми розглянемо основні характеристики і механізми, індукції клітинного старіння, приділивши особливу уваги залежних від стрес-фактора відмінностям активуються при клітинному старінні сигнальних каскадів. Клеточное старение является клеточным ответом на стресс в виде перманентного ареста пролиферации, сопровождаемого комплексом фенотипических изменений. Наиболее важными признаками клеточного старения являются отсутствие синтеза ДНК, увеличение активности ассоциированной со старением β-галактозидазы и увеличение экспрессии ингибиторов циклин-зависимых киназ. Эти универсальные маркеры клеточного старения характерны также и для других типов ареста пролиферации клеток. Наряду с универсальными маркерами клеточное старение имеет дополнительные характеристики, которые в большей степени зависят от индуцирующего старение фактора и/или типа клеток. В этом обзоре мы рассмотрим основные характеристики и механизмы, участвующие в индукции клеточного старения, уделив особое внимания зависящим от стресс-фактора различиям активируемых при клеточном старении сигнальных каскадов.